THE INFLUENCE OF ARABIC LANGUAGE STUDENTS’ EDUCATIONAL BACKGROUNDS ON THE LEARNING OUTCOMES OF BASIC GRAMMAR AT THE STATE ISLAMIC UNIVERSITY OF IMAM BONJOL PADANG - Sri Indah Lestari; Ifkar Rasyid; Yasmadi Yasmadi; Muhammad Taufiqurrahman; Hafid Arsyad (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Arabic language students face difficulties when studying al qawaid al asassiyah in the Nahwu course due to the diversity of educational backgrounds within a single class, which includes graduates from general high schools (SMA/SMK), Islamic high schools (MA), and Islamic boarding schools (Pesantren). This research aims to examine the influence of educational background on the learning outcomes of Arabic language students in al qawaid al asassiyah at UIN Imam Bonjol Padang and to suggest solutions for both students and instructors when encountering these challenges. Using a quantitative, descriptive approach, the findings show a significant impact of educational background on learning outcomes, as indicated by the varying average final scores: 50 for SMA alumni, 56.68 for MA alumni, and 61.49 for Pesantren alumni.